Battery collection in municipal waste management in Japan: Challenges for hazardous substance control and safety. (May 2015) - Terazono, Atsushi; Oguchi, Masahiro; Iino, Shigenori; Mogi, Satoshi
Highlights: Consumers need to pay attention to the specific collection rules for each type of battery in each municipality in Japan. 6–10% of zinc carbon and alkaline batteries discarded in Japan currently could be regarded as containing mercury. Despite announcements by producers and municipalities, only 2.0% of discarded cylindrical dry batteries were insulated. Batteries made up an average of 4.6% of the total collected small WEEE under the small WEEE recycling scheme in Japan. Exchangeable batteries were used in almost all of mobile phones, but the removal rate was as low as 22% for mobile phones. Abstract: To clarify current collection rules of waste batteries in municipal waste management in Japan and to examine future challenges for hazardous substance control and safety, we reviewed collection rules of waste batteries in the Tokyo Metropolitan Area. We also conducted a field survey of waste batteries collected at various battery and small waste electric and electronic equipment (WEEE) collection sites in Tokyo. The different types of batteries are not collected in a uniform way in the Tokyo area, so consumers need to pay attention to the specific collection rules for each type of battery in each municipality. In areas where small WEEE recycling schemes are being operated after the enforcement of the Act on Promotion of Recycling of Small Waste Electrical and Electronic Equipment in Japan in 2013, consumers may be confused about the need for separating batteries from small WEEE (especially mobile phones). Our field survey of collected waste batteries indicated that 6–10% of zinc carbon and alkaline batteries discarded in Japan currently could be regarded as containing mercury. More than 26% of zinc carbon dry batteries currently being discarded may have a lead content above the labelling threshold of the EU Batteries Directive (2006/66/EC). In terms of safety, despite announcements by producers and municipalities about using insulation (tape) on waste batteries to prevent fires, only 2.0% of discarded cylindrical dry batteries were insulated. Our field study of small WEEE showed that batteries made up an average of 4.6% of the total collected small WEEE on a weight basis. Exchangeable batteries were used in almost all of mobile phones, digital cameras, radios, and remote controls, but the removal rate was as low as 22% for mobile phones. Given the safety issues and the rapid changes occurring with mobile phones or other types of small WEEE, discussion is needed among stakeholders to determine how to safely collect and recycle WEEE and waste batteries.